2012
DOI: 10.1155/2012/952504
|View full text |Cite
|
Sign up to set email alerts
|

Rhein Induces Apoptosis in Human Breast Cancer Cells

Abstract: Human breast cancers cells overexpressing HER2/neu are more aggressive tumors with poor prognosis, and resistance to chemotherapy. This study investigates antiproliferation effects of anthraquinone derivatives of rhubarb root on human breast cancer cells. Of 7 anthraquinone derivatives, only rhein showed antiproliferative and apoptotic effects on both HER2-overexpressing MCF-7 (MCF-7/HER2) and control vector MCF-7 (MCF-7/VEC) cells. Rhein induced dose- and time-dependent manners increase in caspase-9-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 35 publications
2
35
0
Order By: Relevance
“…To this end, we focused on microglia as microglia/macrophages are the main cells that constitute the glioma microenvironment and are known to express CD38 . As the previous studies showed that in some cells rhein has cytotoxic effect, we first examined the effect of increasing concentrations of rhein on N9 microglia cell viability. The results obtained are shown in Figure a .…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we focused on microglia as microglia/macrophages are the main cells that constitute the glioma microenvironment and are known to express CD38 . As the previous studies showed that in some cells rhein has cytotoxic effect, we first examined the effect of increasing concentrations of rhein on N9 microglia cell viability. The results obtained are shown in Figure a .…”
Section: Resultsmentioning
confidence: 99%
“…HER2-containing dimers have long halflives and exhibit strong and persistent signaling due to both slow ligand dissociation and internalization [7]. Thus, HER2 excessively stimulates survival and mitogenic pathways [8,9], resulting in overall deregulated signaling [10], reduced apoptosis [11], prolonged cell survival [12], and increased metastatic potential [13].…”
Section: Introductionmentioning
confidence: 99%
“…It can apparently demonstrates the efficacy, side effects and toxicity of medicines as a whole; however, it is high cost, lowthroughput and cannot be used for the direct screening of bioactive components in TCMs (Huang et al, 2004). Cell-, receptor-and enzyme-based screenings have gradually become fundamental for modern high-throughput screening of bioactive compounds in medicinal plants (Chang et al, 2011;de Beer et al, 2011). Recently, bioactivity-based LC-MS/ MS identification technology has attracted more and more attention owing to its high throughput, high specificity and low cost (Hou et al, 2012;Su et al, 2010).…”
Section: Introductionmentioning
confidence: 99%